Influence of Operational Costs, Company Size, and Operational Leverage on Property & Real Estate Sector Profitability Listed on the Indonesia Stock Exchange - Erisa, Arifah Diah Putri; Sundari, Siti (Manunggal Halim Jaya, 2025)
A company's profitability is one of the key indicators in assessing financial performance, which can attract investor interest and influence strategic decision-making. This study examines and analyzes the influence of operating costs, company size, and operating leverage on the profitability of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). The research population consists of 92 companies, and a purposive sampling technique resulted in 20 companies being selected as the sample. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method through SmartPLS 3.0 software. The study's results indicate that increased operating leverage improves profitability in the property and real estate sector listed on the Indonesia Stock Exchange (IDX), while higher operating costs negatively impact profitability. However, company size does not contribute to profitability. This research is expected to assist property and real estate companies utilize resources (assets) to enhance profitability. Future researchers should consider other variables, such as capital structure, liquidity levels, or dividend policy, to broaden the understanding of corporate profitability factors and explore potential regional variations in the property and real estate sector.